Avatar, the last airbender. The complete book 3 collection [videorecording (DVD)] = Jiang shi shen tong - DiMartino, Michael Dante; Konietzko, Bryan (Paramount Pictures : Nickelodeon, 2008)
Avatar Aang has survived the terrible battle with Azula and now faces new challenges as he and his friends enter the Fire Nation. They must find and defeat Firelord Ozai, who seeks to spread his dominion across the four nations. Without a master to help, Aang must learn a lot of bending.